Acute Immunological Biomarkers for Predicting Chronic Rheumatologic Disease After Chikungunya Virus Infection - Anyela Lozano-Parra; Víctor Herrera; Luis Ángel Villar; Silvio Urcuqui-Inchima; Juan Felipe Valdés-López; Elsa Marina Rojas Garrido (Tropical Medicine and Infectious Disease)
Early biomarkers are needed to predict the long-term persistence of rheumatical symptoms in patients infected with Chikungunya virus (CHIKV). This nested case-control study aimed to assess immunological factors during the early phases of CHIKV infection to predict the risk of post-CHIK chronic rheumatism (pCHIK-CR) in adult patients of two prospective cohorts. We evaluated 46 febrile patients (median age: 33.5 years; IQR: 19 years; women: 50.0%) with CHIKV infection confirmed during the 2014–2015 outbreak in Santander, Colombia. The participants were classified by a rheumatologist as either cases (pCHIK-CR) or controls (WoRM, without rheumatical manifestations). We quantified serum levels of IL-4, IL-6, IL-8/CXCL-8, IL-27, CCL-2, CXCL-9, CXCL-10, and IgG using Luminex and ELISA assays during the acute and subacute phases of infection. Then, we evaluated the association of these immune factors with the case-control status using piecewise logistic regression adjusted for age and sex. There were non-linear associations between IL-8/CXCL-8, CXCL-9, and CXCL-10 with pCHIK-CR. Increases in the levels of IL-8/CXCL-8 (<35.7 pg/mL), CXCL-9 (≥6000 pg/mL), and CXCL-10 (≥36,800 pg/mL) were significantly associated with a reduced risk of pCHIK-CR (adjusted ORs: 0.85, 0.96, and 0.94, respectively). These results suggest that increases in IL-8/CXCL-8, CXCL-9, and CXCL-10 levels, measured in the early stages of CHIKV infection, may predict a chronic disease risk. This suggests the possibility that an early and strong immune response could contribute to enhancing CHIKV control and potentially reduce the risk of persistent joint symptoms. Given their expression patterns and timing, these three immune factors may be considered promising biomarker candidates for assessing the risk of chronic rheumatologic disease. These findings should be considered as exploratory and validated in additional cohort studies.